INTERAKSI WANITA IDDAH MELALUI MEDIA SOSIAL - Sunarto, Muhammad Zainuddin; Liana, Karmilah (JURNAL ISLAM NUSANTARA, 2020)
The legal aspect for women who are undergoing the iddah period, the correlation to communication via social media is not found valid arguments related to this case, but four fiqh experts (madzhab) have agreed that women who are undergoing 'iddah death period are not allowed to leave the house except under these conditions. an emergency or in a state of urgency to leave the house, even though they have different opinions about the time and limit of the iddah prohibition. This study examines the legal aspects of women who are undergoing ‘Iddah’ correlation to interactions on social media. This research is a library research, namely through the study of secondary data sources consisting of various references, especially books that are closely related to the discussion. The results of the study concluded that women who are undergoing 'iddah' are not allowed to use any social media to communicate with men who are not mahroms and without an urgent need, unless the communication is only intended for the benefit of life and does not conflict with the principle of benefit.